MODERNIZATION OF POSTGRADUATE MEDICAL EDUCATION AS A FACTOR OF REALIZATION OF PERSONNEL POLICY IN HEALTH CARE - A. D. Kaprin; A. A. Kostin; B. T. Ponomarenko; O. V. Gridnev; Yu. V. Samsonovry (Исследования и практика в медицине)
Abstract:In the article they discuss the status and problems of modernization of doctors in the context of the implementation of the state policy in the national system of Russian health care. The author presents judgments about the role and certification of postgraduate training of physicians, the directions of the improvement of professional education of doctors.